Ten year neurocognitive trajectories in first-episode psychosis - Barder, Helene E.; Sundet, Kjetil; Rund, Bjørn; Evensen, Julie; Haahr, Ulrik; Hegelstad, Wenche; Joa, Inge; Johannessen, Jan Olav; Langeveld, Johannes; Larsen, Tor Ketil; Melle, Ingrid; Opjordsmoen, Stein; et al. (Frontiers in Human Neuroscience, 2013)
Objective: Neurocognitive impairment is commonly reported at onset of psychotic disorders. However, the long-term neurocognitive course remains largely uninvestigated in first episode psychosis (FEP) and the relationship to clinically significant subgroups even more so. We report 10 year longitudinal neurocognitive development in a sample of FEP patients, and explore whether the trajectories of cognitive course are related to presence of relapse to psychosis, especially within the first year, with a focus on the course of verbal memory. Method: Forty-three FEP subjects (51% male, 28±9 years) were followed-up neurocognitively over five assessments spanning 10 years. The test battery was divided into four neurocognitive indices; Executive Function, Verbal Learning, Motor Speed, and Verbal Fluency. The sample was grouped into those relapsing or not within the first, second and fifth year. Results: The four neurocognitive indices showed overall stability over the ten year period. Significant relapse by index interactions were found for all indices except Executive Function. Follow-up analyses identified a larger significant decrease over time for the encoding measure within Verbal Memory for patients with psychotic relapse in the first year (F (4,38)=5.8, p=0.001, η2=0.40) Conclusions: Main findings are long-term stability in neurocognitive functioning in first episode psychosis patients, with the exception of verbal memory in patients with psychotic relapse or non-remission early in the course of illness. We conclude that worsening of specific parts of cognitive function may be expected for patients with on-going psychosis, but that most patients should expect no change in cognitive performance during the first 10 years after being diagnosed.